DIGITAL TECHNOLOGIES IN TEACHING PHYSICS: AN ANALYSIS OF EXISTING PRACTICES - Yurchenko, Artem; Khvorostina, Yurii; Shamonia, Volodymyr; Semenikhina, Olena (Physical and Mathematical Education, 2023)
Formulation of the problem. Teachers in Ukraine, due to the lack of funding for schools with equipment for conventional physical experiments, are looking for alternative ways to teach physics, including the use of digital technologies. The degree of their influence on learning outcomes is not unambiguous, so it is advisable to analyze the existing practices of their use. The study aims to characterize the state of the introduction of digital technologies and tools in teaching physics, which are presented in scientific publications and existing practices.Materials and methods. The research methodology involved analyzing and systematizing scientific publications to identify individual educational trends in the use of DT in teaching physics, as well as conducting surveys and studying teachers' opinions through conversation. The survey involved physics teachers and students (Sumy region, Ukraine). The total number of respondents is 106 people.Results. The following directions of using digital technologies in teaching physics have been identified: the use of digital tools as tools for studying physical processes; the use of applications for solving physical problems; the use of virtual and digital physics laboratories; use of virtual and augmented reality teaching physics; use of specialized environments for modeling physics processes. Conclusions. The analysis of theoretical developments proves the spread of experience in introducing digital technologies in teaching physics, but the practical state of their use in Ukraine indicates isolated practices. The reasons are the weak material and technical base; the ignorance of how to use DT in teaching physics; the unwillingness of working teachers to use digital technologies. So, the urgent task of universities is the proactive training of physics teachers who will be familiar with various digital technologies and means of teaching physics and are ready to introduce effective methods of their use in their professional activities.
Keywords: teaching physics; digital technologies in teaching physics; virtual physics laboratories; computer simulations; physics teacher